Static and Fatigue Characterization of Nomex Honeycomb Sandwich Panels - Keskes Boualem (Pamukkale University Journal of Engineering Sciences, 2013)
The main benefits of using the sandwich concept in structural components are the high stiffness, good fatigue resistance and low weight ratios. Recent advances in materials and construction techniques have resulted in further improvement and increased uniformity of the sandwich composite properties. In order to use these materials in different applications, the knowledge of simply their static properties alone is not sufficient but additional information on their fatigue properties and durability are required. In this paper, first static and fatigue tests on four points bending of nomex honeycomb composite sandwich panels have been performed. Load/displacement and S-N fatigue curves are presented and analysed. Fatigue failure and damage modes are observed with an optical microscope and are discussed. The second is to address such fatigue behaviour by using a damage model and check it by experimentation. This fatigue damage model is based on stiffness degradation, which is used as a damage indicator. Two non-linear cumulative damage models derived from the chosen stiffness degradation equation are examined with assumption of linear Miner's damage summation. Predicted results are compared with available experimental data.